RECURRENCE IN NON-EPITHELIAL OVARIAN CANCER PATIENTS AT RSUP DR. KARIADI SEMARANG - Badia, Gabriele Emi; Iskandar, Teuku Mirza; Suhartono, Suhartono (Faculty of Medicine, Diponegoro University, 2023)
BACKGROUND: Non-epithelial ovarian cancer is a very rare type, accounting for less than 10% of ovarian cancers. This type of cancer originates from germ cells or stromal-sex cord cells. Disease-free survival (DFS) in cancer is the length of time after primary treatment for cancer ends so that patients survive without signs or symptoms of cancer. Recurrence is the return of cancer that has been declared in remission, usually after a certain period in which cancer cannot be detected. Cancer can return to the same place (primary) or other parts of the body. Ovarian cancer is a disease with a high probability of recurrence, after achieving a complete response to chemotherapy, >70%. Assessment of the recurrence rate is one of the ways used to assess the effectiveness of therapyAIM: Knowing the incidence of recurrence in patients with non-epithelial ovarian cancer who have received operative therapy with or without adjuvant chemotherapyMETHOD: Descriptive study with a case series research design and analytical works. The research sample was 50 non-epithelial ovarian cancer patients who were treated at RSUP Dr. Karadi Semarang from 2018-2019 who met the inclusion criteria and did not have exclusion criteria, 22 patients were loss of follow up during observation. The data collection technique used is total sampling. Data analysis was performed using the Chi-Square test with a significance level of p<0.05.RESULT: The most reported types of non-epithelial ovarian cancer were granulosa (39.3%), dysgerminoma (21.4%), yolk sac (17.9%), and mixed germ cell (17.9%). Most of the cancer cases are progressive (60.7%). There were 3 recurrence incidents happen during observation period, 2 patients with granulosa cell tumor in >50 years age group and 1 patient with Yolk Sac cell tumor in 20-50 years age group. Higher survival rates were found for tumor residues <2cm compared to >2cm at 6 months (54.5% vs 45.5%), 12 months (54.5% vs 36.4%), 18 months (45.5% vs 36.4%), and 24th month (45.5% vs 36.4%).CONCLUSION: Optimization of surgery depends on the type of non-epithelial ovarian cancer cells, age, and the stage when the diagnosis was first established to be a factor in the incidence of recurrence.